Observation of Marine Areas (Çandarlı and Gökova Bays) and Their Biodiversity - Sevilay Öztürk; Oğuz Kurt (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This study aimed to investigate to determine the number and biodiversity of species (especially seaweed populations) in the Çandarlı and Gökova Bays. Çandarlı and Gökova Bays are defined as "Special Environmental Protection Area (SEPA)" by the Ministry of Environment and Forestry of the Republic of Turkey, Special Environmental Protection Agency Presidency. For this purpose, in the study, i) description of habitats and facies in the studied areas, ii) determination of the number and diversity of species, iii) retrieval of underwater photo recordings, operations were carried out. The approach of collecting these data in such a way as to make comparisons and comments, especially for the future, has been followed. The literature shows that the existing ecological conditions and habitat characteristics of the areas restricted to SEPA and fisheries are studied. Thus, a comprehensive database is developed that will be extremely useful in terms of future works. On the other hand, the studies carried out are particularly inadequate for marine algae (macroalgae) in the related areas. As a result of the study, a total of 316 taxa were identified and observed, including 192 marine algae (20 Cyanobacteria, 54 Phaeophyceae, 93 Rhodophyta, 25 Chlorophyta), 3 seagrasses, 70 invertebrates (9 Porifera, 13 Cnidaria, 2 Annelida, 19 Mollusca, 16 Arthropoda, 10 Echinodermata, 2 Tunicata) and 51 fish (2 Chondrichthyes, 49 Osteichthyes).